Potentiation of antifungal activity of terbinafine by dihydrojasmone and terpinolene against dermatophytes. (1st March 2021) - Pinto, Â.V.; de Oliveira, J.C.; Costa de Medeiros, C.A.; Silva, S.L.; Pereira, F.O.
Abstract: Dermatophytoses are infections that affect keratinized tissues. Their main etiologic agents are fungi of the genera Microsporum and Trichophyton . The emergence of resistant fungi and the clinical relevance of dermatophytosis have encouraged studies that aim to increase the arsenal of drugs or act on mechanisms that confer multiple drug resistance. This study investigated the modulating activity of terbinafine promoted by dihydrojasmone and terpinolene against Microsporum canis LM 216, Trichophyton interdigitale H6 and T. interdigitale Δ mdr2 . The minimum inhibitory concentration (MIC) of test drugs was determined by broth microdilution. The effect of the drugs tested on plasma membrane functionality was analysed. Terbinafine MIC was determined in sub‐inhibitory concentrations of monoterpenes. Finally, it was performed an association study with terbinafine and monoterpenes. Dihydrojasmone presented lower MIC values than terpinolene. All fungi were sensitive to terbinafine, starting at 1 μ g ml −1 . All tested drugs increased K + release ( P < 0·05), affecting the functionality of the plasma membrane. Dihydrojasmone modulated the sensitivity of all strains against terbinafine, and terpinolene modulated the sensitivity of M. canis LM 216 and T. interdigitale Δ mdr2 . The monoterpenes and terbinafine drug associations presented synergism. In conclusion, the results suggest that the dihydrojasmone and terpinolene are promising antifungal agents that potentiate the antifungal activity of terbinafine against dermatophytes.